An associative account of how the obesogenic environment biases adolescents' food choices. (1st January 2016) - Watson, P.; Wiers, R.W.; Hommel, B.; Ridderinkhof, K.R.; de Wit, S.
Abstract: Adolescents and children are the targets of much food advertising, the majority of which is for unhealthy snacks. Although the effects of advertising on food preferences and consummatory behavior are well documented, our understanding of the underlying mechanisms is still limited. The present study investigates an associative (ideomotor) mechanism by which exposure to rewarding (snack) outcomes may activate behavior that previously resulted in these rewards. Specifically, we used a computerized task to investigate whether exposing adolescents to food pictures directly, or to Pavlovian cues predictive of those food pictures, would bias their subsequent responses towards the presented/signaled food. Furthermore, we assessed whether this effect was particularly pronounced with palatable, high-calorie snacks (crisps and chocolate) relative to low-calorie snacks (tomatoes and cucumber). In two experiments, adolescents learnt that certain key presses would yield particular food pictures – some high calorie and others low calorie – before learning Pavlovian associations between cues (cartoon monsters) and these same food pictures. Subsequently, in a response-priming test, we examined the extent to which the food pictures and Pavlovian cues spontaneously primed the previously associated response. The results show that we replicated, in adolescents, previous demonstrations of ideomotor response priming in adults: food pictures biased responding towards the response that previously yielded them, and this effect transferred to the Pavlovian cues. Furthermore, the priming effect was significantly stronger for high-calorie rewards than for low-calorie. These findings indicate that the ideomotor mechanism plays an important role in the detrimental effect of our obesogenic environment, with its plethora of unhealthy food reminders, on adolescents' food-related choices.